Application of Taguchi and Analysis Hierarcy Process Methods for Furan Design on Metal Casting Industry - Hasibuan, Abdurrozzaq; Parinduri, Luthfi; Krianto Sulaiman, Oris; Elviani, Sri; Asaad, Mhd.; Napid, Suhardi; Ekalestari, Susi; Hasibuan, Masnilam; ., Yusmartato (International Journal of Engineering and Technology, 2018)
In the preparation of furan the raw material used are, Silica Sand, Resin, and Catalyst. Some problem that occurs are high level of water, high level of sour, high level of clay, unsuitable distribution, and low permeability. All those problems above make the power of furan not suitable with the target that has been stated, so that furan can easily be broken, cracked, and do not stand with high temperature and its power becomes weak. The result of this research is that the optimal combination based on the highest TOPSIS score is A1 B2 C3 with the composition of Resin 1.3%, Catalyst 22.5% and new sand 15% + reclaim sand 85%. The coefficient of loss function compression strength is 4.611,11 and 10.375 for the shear strength. The raising quality based on the confirmation experiment is 0.1018 for the compression strength and 0.2339 for the shear strength. The value of S/N in the confirmation experiment for the compression strength is 20.5817 and 23.0480, in which both numbers are in the trust interval limitation that has been decided. It shows that TOPSIS procedure is able to increase furan quality for both responses, that is compression strength response, and shear strength response all at once in one parameter setting.Â Â